2013
DOI: 10.14712/18059694.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Properties of Niti Closed Coil Springs – Force Degradation and Force Regeneration Over Time, Viscous Properties

Abstract: Springs should be mechanically stabilized before their application. The degree of force degradation over time is insignificant for mechanically stabilized springs. Degradation or regeneration of force over time, mechanical stabilization or micromovements in the mouth don't cause any transition between individual stress-strain curve phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…4 The entire process of extension and verification of the forces released by the springs was repeated five-time for each spring tested. The methodology proposed in the present study had previously been adopted in the studies of Bezrouk et al 2 and Maganzini et al 4 The nickel-titanium closed springs were evaluated by means of traction forces in a universal test machine EMIC DL 200 MF (Instron®, São José dos Pinhais, SP, Brazil) programmed with a speed of 10 mm/minute. Data analyses and collection were obtained by means of the software Tesc version 3.04 (EMIC, Curitiba/PR, Brazil).…”
Section: Sample Preparation and Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The entire process of extension and verification of the forces released by the springs was repeated five-time for each spring tested. The methodology proposed in the present study had previously been adopted in the studies of Bezrouk et al 2 and Maganzini et al 4 The nickel-titanium closed springs were evaluated by means of traction forces in a universal test machine EMIC DL 200 MF (Instron®, São José dos Pinhais, SP, Brazil) programmed with a speed of 10 mm/minute. Data analyses and collection were obtained by means of the software Tesc version 3.04 (EMIC, Curitiba/PR, Brazil).…”
Section: Sample Preparation and Selectionmentioning
confidence: 99%
“…6 A previous study 4 drew attention to the analysis of the catalog of numerous commercial brands, which highlighted distinct terms on their packages, such as "ultralight", "light", "medium", "heavy", and "extra heavy", or listed "constant force values" such as "100 gf", "150 gf", and "200 gf", and even identified the springs by the diameter of the lumen, such as "0.010", "0.011" and "0.012". However, possible biases of previous studies 2,3 were found in the performance of traction tests to obtain the forces released by the springs, with a lack of attention to, and questions about these terms. Furthermore, there is no comparison of the results of studies with these standardized force values provided on the labels by the manufacturers.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We tested ten different types of springs from five manufacturers (GAC, 3M, Dentaurum, OrthoOrganizers, AmericanOrthodontics) (table 1). For each type of spring, we performed a number of stability [16] and destructive tests to discover the optimal plateau phase deployment and measurement limits for safe spring operation. Fifteen samples of each spring type were tested.…”
Section: Experimental Part Test Springsmentioning
confidence: 99%